(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cancer of the oral cavity and oropharynx in clinical practice is considered as a single oncopathology, treated as oropharyngeal cancer (OPR). This pathology occupies the 2nd place in the incidence rate among head and neck tumors in the Russian Federation [1]. The incidence of OFR in the Russian Federation is not the same: in the industrial districts, which include the Rostov region, it is high, which put the region in the top ten regions with a high incidence of this pathology.